(untitled) (International Journal of Food and Nutritional Sciences, 2019)
To Reduce the usage of the Concrete content we are studying the different types of materials strength as an admixture and later if we are getting good results the studies will be forwarded to partial replacement and finally if possible the complete replacement of cement. This is the study with of the continuation of the Influence of thermal dust as an admixture with 0%,2% and 4% admixture and the continuation is carried forward. The experimental study of bottom ash on normal strength concrete grade for 6% ,8% and 10% replacement cube were also prepared respectively.